Demography of Grazed Tussock Grass Populations in Patagonia - Oliva, Gabriel Esteban (2005)
The cover of Festuca gracillima (coirón fueguino), a native tussock grass that dominates grass steppes of Southern Patagonia and Tierra del Fuego, has diminished under continuous sheep grazing. This loss is a concern, because it also reduces forage availability in winter, biodiversity, and soil stability. In the present study, the hypothesis that tussock grass birth and mortality rates are balanced only under moderate-grazing or exclusion regimes was tested with two 5-year records of demographic data obtained from 3 sheep grazing regimes: exclosure (no grazing), low (0.0348 AU·ha−1·y−1, where AU represents animal units equivalent to the consumption of a 450-kg cow), and high (0.1043 AU·ha−1·y−1). Tussocks were outlined in photographs and marked in the field at two 5-year intervals. The initial total number of plants for the 3 grazing regimes (n = 358) increased to 384 plants at the end of the 10-year period. No recruitment from seed was observed; plant number changed as a balance of yearly rates of tussock mortality (1.48%), amalgamation (0.75%), and subdivision (2.04%). Intensely grazed populations showed greater (2.13%) mortality rates than ungrazed (1.20%) or moderately grazed (0.78%) populations. Tussocks in intensely grazed populations were smaller (167 cm2·plant−1) than those in moderately grazed (197 cm2·plant−1) or ungrazed (300 cm2·plant−1) populations. Transition matrices showed eigenvalues of 0.701 (high grazing), 0.794 (exclosure), and 0.876 (low grazing). All growth rates of demographic models were negative; the largest rate of population decrease was found under high-intensity grazing, for which projections show that half the tussocks would be lost in 37 years. Under low-intensity grazing and exclosure, a similar tussock loss would take place in 87 and 74 years, respectively. Results show 1) the importance of vegetative processes for tussock demography, 2) the extremely slow dynamics of population changes, and 3) that tussocks may suffer increased mortality as a consequence of subdivision or fragmentation, a process that can be viewed as a small-scale example of the generalized effect of patch subdivision under grazing.